2018
DOI: 10.1080/18902138.2018.1533272
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Mangetar Trap’? Work, family and Pakistani migrant husbands

Abstract: Contemporary immigration from Pakistan to the UK often takes the form of marriage migration, as substantial numbers of British men and women of Pakistani ethnicity marry partners from Pakistan. Drawing on quantitative and qualitative evidence, this paper explores experiences of Pakistani men migrating to the UK through marriage, revealing a complex of social and economic pressures in the early months and years post-migration, here referred to as the 'Mangetar Trap'. Migration can have contradictory implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…There are further studies, indicating that contemporary immigration from Pakistan to the United Kingdom, which frequently takes place in form of a marriage migration, reveals a complex of social and economic pressures in the early months and years after migration. In men, this kind of migration may result in contradictory implications for masculinity [24]. Research also indicates that migration marriages may offer socioeconomic bene ts in the destination country, if the opportunity of migration attracts a more highly educated spouse.…”
Section: Discussionmentioning
confidence: 99%
“…There are further studies, indicating that contemporary immigration from Pakistan to the United Kingdom, which frequently takes place in form of a marriage migration, reveals a complex of social and economic pressures in the early months and years after migration. In men, this kind of migration may result in contradictory implications for masculinity [24]. Research also indicates that migration marriages may offer socioeconomic bene ts in the destination country, if the opportunity of migration attracts a more highly educated spouse.…”
Section: Discussionmentioning
confidence: 99%
“…Research on migrants and their aspirations has shown that genderspecific normse.g. men as the main breadwinners (Charsley and Ersanilli 2019) and women as care-givers (Scheibelhofer 2018)play a crucial role in shaping migrants' future aspirations. Migration involves some degree of dislocation from the cultural and social contexts in which gender ideals and practices are generated, which may result in a loss or gain of power and status (Charsley and Ersanilli 2019).…”
Section: Introductionmentioning
confidence: 99%
“…men as the main breadwinners (Charsley and Ersanilli 2019) and women as care-givers (Scheibelhofer 2018)play a crucial role in shaping migrants' future aspirations. Migration involves some degree of dislocation from the cultural and social contexts in which gender ideals and practices are generated, which may result in a loss or gain of power and status (Charsley and Ersanilli 2019). In particular, work and family are key domains in which tensions around gendered aspirations arise (Charsley and Ersanilli 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations